A Low-Cost Instrument for Dry Particle Fusion Coating of Advanced Electrode Material Particles at the Laboratory Scale. Issue 11 (6th July 2020) - Geng, Chenxi; Trussler, Simon; Johnson, Michel B.; Zaker, Nafiseh; Scott, B.; Botton, Gianluigi; Dahn, J. R.
Abstract : Surface coating is an approach used to improve capacity retention of electrode materials for lithium-ion batteries. Dry particle fusion is a relatively new approach for applying coatings on particles. In this work, we introduce a low-cost dry particle fusion instrument that was constructed in house. The operation and performance of the machine is demonstrated by dry particle fusion coating of alumina on Ni(OH)2 and alumina and LiFePO4 on LiNi0.8 Co0.15 Al0.05 O2, respectively. The hammer temperature vs time during dry particle fusion is used to monitor the process. Particle size distribution results demonstrate that the original core particles are not fractured by the coating process. SEM images show the morphology of particles before and after dry particle fusion coating and cross-sectional SEM/EDS images show the uniformity of the coating. Coin cell testing results show that dry particle fusion with suitable coating materials, at the laboratory scale using this instrument, is effective in improving capacity retention.